Tantangan dan Prospek Pengendalian Riba dalam Transaksi di E-Commerce (Studi Kasus Transaksi Jual Beli Menggunakan Shopee Paylater) - Cinta Rahmi; Chiesa Ikhwan Vizizou; Bagus Prastyo; Ahmad Faisal Amri; Muhammad Fariza Al Farisi; Muhammad Faiz Rahmat Arrizzy (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
Even in this era of progress and globalization, the concept of usury is still a topic of debate in the context of global finance. According to scholars, in the context of Islamic finance, usury is expressly prohibited in the Koran. Apart from that, usury also has negative impacts such as exploitation of borrowers and economic inequality. We need to control usury, even though it is difficult. This study discusses the challenges and prospects of controlling usury in the e-commerce transaction sector in ShopeePay Later lending practices. The research method used is a qualitative method using literature review techniques. These findings highlight the challenges of managing usury at ShopeePay Later, namely high interest rates for late bill payments, unclear understanding of customers regarding payment terms and mechanisms, payment abuse. On the other hand, the way to curb usury is to increase information transparency, implement financial education programs, understand healthy debt management, and implement financial education programs. And for customers, that is by creating a balance between income and expenses.